Утворіть тотожність:
2p-q/pq - 1/p+q * ( p/q - q/p ) =

Gogogogh Gogogogh    2   01.11.2019 23:23    1

Ответы
vxtrxxx vxtrxxx  10.10.2020 10:53

Объяснение:

\tt\displaystyle \[\frac{{2p-q}}{{pq}}-\frac{1}{{p+q}}*\left( {\frac{p}{q}-\frac{q}{p}} \right)=\frac{{2p-q}}{{pq}}-\frac{1}{{p+q}}*\left( {\frac{{{p^2}-{q^2}}}{{pq}}} \right)= \frac{{2p-q}}{{pq}}-\frac{1}{{p+q}}*\frac{{(p-q)(p+q)}}{{pq}}=\frac{{2p-q}}{{pq}}-\frac{{p-q}}{{pq}}=\frac{{2p-q-p+q}}{{pq}}=\frac{p}{{pq}}=\boxed{\frac{1}{q}}\]

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра